Nuclear reactions how nuclear-armed states behave - Bell, Mark (Researcher) (Cornell studies in security affairs., 2021)
"This book examines the ways in which states change their foreign policies when they acquire nuclear weapons, using case studies of the United Kingdom, South Africa, and the United States"--